Direct determination of the collective pinning radius in the cuprate superconductor Bi2 Sr2 CaCu2 O8+ delta - Dolz, M.I. (2010)
Fil: Dolz, M.I. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina